Separated by a Common Language: How the Nature of Code Differences Shapes Communication Success and Code Convergence - Koçak, Özgecan; Puranam, Phanish (Management Science, 2022)
Coordinated action within and beween organizations is easier when individuals share communication codes—mappings between stimuli and labels. Because codes are specific to the groups within which they arise as conventions, collaboration across organizational units that have developed their own distinctive codes is often difficult. However, not all code differences are equal in their implications for communication difficulty and the capacity of individuals starting out with different codes to develop a shared code. Using computational models, we develop a theory about the nature of differences in initial communication codes and how they impact convergence on a common code. Our results show that the difficulty of code convergence lies not as much in learning new codes as in unlearning existing ones. The most severe challenges to communication stem from “code clashes” where codes contain different mappings between the same labels and stimuli. Furthermore, clashes that arise when agents have developed their individual codes in different task environments but draw on a common set of labels are likely to be the hardest to recover from, reflecting the perils of being “separated by a common language.” This paper was accepted by Lamar Pierce, organizations.